Interconnected Two‐dimensional Arrays of Niobium Nitride Nanocrystals as Stable Lithium Host. Issue 1 (14th October 2020) - Xiao, Xu; Yao, Wei; Tang, Jun; Liu, Chuanfang; Lian, Ruqian; Urbankowski, Patrick; Anayee, Mark; He, Shijie; Li, Jianmin; Wang, Hao; Gao, Yu; Wei, Yingjin; et al.
Abstract: The cycle life of rechargeable lithium (Li)‐metal batteries is mainly restrained by dendrites growth on the Li‐metal anode and fast depletion of the electrolyte. Here, we report on a stable Li‐metal anode enabled by interconnected two‐dimensional (2D) arrays of niobium nitride (NbN) nanocrystals as the Li host, which exhibits a high Coulombic efficiency (>99 %) after 500 cycles. Combining theoretical and experimental analysis, it is inferred that this performance is due to the intrinsic properties of interconnected 2D arrays of NbN nanocrystals, such as thermodynamic stability against Li‐metal, high Li affinity, fast Li + migration, and Li + transport through the porous 2D nanosheets. Coupled with a lithium nickel–manganese–cobalt oxide cathode, full Li‐metal batteries were built, which showed high cycling stability under practical conditions – high areal cathode loading ≥4 mAh cm −2, low negative/positive ( N/P ) capacity ratio of 3, and lean electrolyte weight to cathode capacity ratio of 3 g Ah −1 . Our results indicate that transition metal nitrides with a rationally designed structure may alleviate the challenges of developing dendrite‐free Li‐metal anodes. Abstract : 2D host : A stable Li‐metal anode is enabled by interconnected 2D arrays of niobium nitride nanocrystals as Li host with a high Coulombic efficiency (>99 %) after 500 cycles. Coupled with lithium nickel–manganese–cobalt oxide, the full Li‐metal battery shows long‐term cycling stability under practical conditions.